University students’ perceptions on the effectiveness of online teaching in Malaysia during covid-19 pandemic: A case of the international relations (IR) programme, Universiti Malaysia Sabah (UMS), Malaysia - Diana Peters (Human Resource Management Academic Research Society, 2022)
Since the pandemic outbreak, most of the students of higher learning have to instantaneously adapt to online teaching as part of today’s new norms. Malaysia is also not an exception to this situation. Since March 2020, most of the higher learning students had to undergo lectures and tutorials via online platform for the entire academic year. As a result, various feelings and opinions on the effectiveness of online teaching were ubiquitously discussed particularly on the cognitive ability of the students to comprehend online lectures. Generally, it has been agreed that, the most challenging issue is the internet coverage involving students residing in the interior areas that either have poor or no internet access. Hence, the main objective of this paper is to unravel higher learning students’ perceptions on the effectiveness of online teaching and learning in Malaysia during this pandemic. To achieve this, this paper focuses on undergraduate students from the International Relations (IR) Programme at Universiti Malaysia Sabah (UMS) located in Sabah. Such a selection is due to Sabah being one of the states that is facing enormous challenges to provide internet services for academic learning. The data collection method for this study is a combination of documentary analysis and the online of survey-questionnaires distributed to 100 IR students as the main respondents. From the findings, this paper crucially identifies the students’ internet problems as well as recommends remedies to increase the effectiveness of online teaching at higher learning institutions in Malaysia.